Feminism and Patriarchal Society: An Illustrative Case Study of Sakharam Binder: Unraveling the Interplay of Patriarchy and Feminism in Sakharam Binder (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Feminism talks about equality in every manner but in India where patriarchy has deep as well as strong roots, it seems very difficult to bring harmony and equality in power structures. Patriarchy has caught Indian middle class society in its claws and its grip on society is rigid and dense which adversely affects the lives of females. The oppression faced by females is consequence of male domination and Tendulkar tends to focus on patriarchal society in Sakharam Binder. An attempt has been made in this paper to show how patriarchy and feminism are interconnected and how male domination turns into oppression of woman when inequality and domination enters into power structures.